Exploring the distilled realms: A study on whiskey and the travellers’ motivations - Custódio, C. M.; Bilro, R. G. (Proceedings of Academy of Marketing 2023 Annual Conference and Doctoral Colloquium: From Revolution to Revolutions, 2023)
The study explores the impact of cultural alcoholic beverages, specifically whiskey, on travel motivations. Results from a quantitative research method indicate that both core cultural products and core whiskey products significantly influence the intention to participate in whiskey tourism. The findings suggest that promoting a destination’s reputation as a producer of high-quality cultural alcoholic beverages can enhance its appeal as a tourist destination, and whiskey as a cultural product can motivate tourism.